Application of fast laser deprocessing techniques in the field of semiconductor manufacturing - Zhao, Yuzhe (2016)
With technology scaling of semiconductor devices and further growth of the integrated circuit (IC) design and function complexity, it is necessary to increase the number of transistors in IC chip, layer stack, and process steps. The last few metal layers of Back End Of Line (BEOL) are usually very thick metal lines (>4µm thickness) and protected with hard Silicon Dioxide (SiO2) material that is formed from (Tetra Ethyl Ortho Silicate) TEOS as Inter-Metal Dielectric (IMD). In order to perform physical failure analysis (PFA) on the logic or memory, the top thick metal layers must be removed. It is time consuming to deprocess those thick metal layers and thick IMD layers. In this project, Fast Laser Deprocessing Technique (FLDT) is proposed to remove the BEOL thick and stubborn metal layers for memory PFA. The proposed FLDT is a cost-effective and quick way to deprocess a sample for defect identification in PFA. Besides application on top down layer deprocessing, this project also further explores on cross sectional sample preparation. Cross-sectional analysis is one of the important areas for physical failure analysis. Focus Ion Beam (FIB) and mechanical polish sample preparation are commonly used and necessary techniques in the semiconductor industry and FA company. However, each technique has its own limitation. Mechanical polishing technique easily induces artifact by mechanical force, especially on advance technology node. FIB can eliminate mechanically damaged artifact, but have the limitation on cross-sectional view area. Another potential technique will be plasma FIB, it used very high milling current and fast milling speed. However, it comes with a very high cost and having the contamination issue. The contamination issue greatly affects the low kV Scanning Electron Microscopy (SEM) imaging quality. In recent semiconductor industry FA, low kV SEM imaging is preferable, because high kV imaging will be introduced delamination artifact especially on organic material from packaged sample. In third part of this project, Fast Laser Deprocessing Techniques (FLDT) application is further enhanced on large area cross-sectional FA with fast cycle time and low-cost equipment. This is to prevent on mechanical damaged. In short, the proposed FLDT is a cost-effective and quick way to deprocess a sample for defect identification in cross-sectional FA.